Digital Religious Learning and Virtual Communities: Evolving Confraternal Bonds in Mouride Education in Touba Senegal - Alassane SOW (CV. Yazri Aksara Nusantara, 2026)
The rapid development of digital technology has transformed religious practices and reshaped learning processes within religious communities. In this context, the Mouride community in Touba, Senegal presents a compelling case of how social media is integrated into religious life. This study aims to examine how digital media transform religious learning practices, social relationships, and actor roles within the Mouride community. The study employs a qualitative approach with a case study design, involving approximately twenty purposively selected participants, including religious leaders and community members. Data were collected through in-depth interviews, participant observation on digital platforms, and content analysis, and were analyzed using thematic analysis. The findings reveal that social media function as pedagogical spaces that enable participatory and collaborative learning, while also reshaping confraternal bonds into hybrid forms of online and offline interaction. In addition, actor roles have shifted toward more interactive and inclusive dynamics. This study concludes that digitalization not only expands access to religious learning but also creates dynamic educational ecosystems, while introducing challenges related to authority and the authenticity of religious practices. Perkembangan teknologi digital telah mentransformasi praktik keagamaan dan cara pembelajaran berlangsung dalam komunitas religius. Dalam konteks ini, komunitas Mouride di Touba, Senegal menunjukkan dinamika menarik dalam mengintegrasikan media sosial ke dalam aktivitas keagamaan. Penelitian ini bertujuan untuk menganalisis bagaimana media digital mentransformasi praktik pembelajaran keagamaan, relasi sosial, dan peran aktor dalam komunitas Mouride. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan sekitar dua puluh partisipan yang dipilih secara purposif, terdiri dari tokoh agama dan anggota komunitas. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif pada platform digital, serta analisis konten, dan dianalisis menggunakan teknik analisis tematik. Hasil penelitian menunjukkan bahwa media sosial berfungsi sebagai ruang pedagogis yang memungkinkan pembelajaran partisipatif dan kolaboratif, sekaligus membentuk ulang ikatan konfraternal dalam bentuk relasi hibrida antara daring dan luring. Selain itu, terjadi transformasi peran aktor menuju model yang lebih interaktif dan terbuka. Penelitian ini menyimpulkan bahwa digitalisasi tidak hanya memperluas akses pembelajaran keagamaan, tetapi juga membentuk ekosistem pendidikan baru yang dinamis, sekaligus menghadirkan tantangan terkait otoritas dan autentisitas praktik keagamaan.